2018
DOI: 10.2967/jnumed.118.219097
|View full text |Cite
|
Sign up to set email alerts
|

Principal Components Analysis of Brain Metabolism Predicts Development of Alzheimer Dementia

Abstract: The value of 18 F-FDG PET for predicting conversion from mild cognitive impairment (MCI) to Alzheimer dementia (AD) is currently under debate. We used a principal components analysis (PCA) to identify a metabolic AD conversion-related pattern (ADCRP) and investigated the prognostic value of the resulting pattern expression score (PES). Methods: 18 F-FDG PET scans of 544 MCI patients were obtained from the Alzheimer Disease Neuroimaging Initiative database and analyzed. We implemented voxel-based PCA and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 32 publications
5
51
0
Order By: Relevance
“…Indeed, the KLSE method outperformed the traditional group-level approach for revealing patterns of altered metabolic connectivity predictive of conversion. Our findings of salient connectivity patterns in the parietal and occipital lobes, recapitulate results of previous FDG-PET group-based comparisons [8,25]. In addition, we found that KLSE has considerable intra-group stability for resolving metabolic network organization, and highlights an especially pronounced inter-individual dissimilarity of metabolic connectivity of the parietal lobe of the pMCI group (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, the KLSE method outperformed the traditional group-level approach for revealing patterns of altered metabolic connectivity predictive of conversion. Our findings of salient connectivity patterns in the parietal and occipital lobes, recapitulate results of previous FDG-PET group-based comparisons [8,25]. In addition, we found that KLSE has considerable intra-group stability for resolving metabolic network organization, and highlights an especially pronounced inter-individual dissimilarity of metabolic connectivity of the parietal lobe of the pMCI group (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The Z-statistic for each continuous covariate was used to calculate a hazard ratio (HR) of the risk for conversion as a function of the number of standard deviations of an increase in the covariates. We then performed four multivariable Cox model analyses with age and sex as factors, including the following variables: (1) clinical (MMSE, APOE ε4), (2) metabolic connectome expression (MCE), (3) group-level pattern expression score (PES) [8], and (4) combination of all variables (MMSE, APOE ε4, MCE). To assess the model's validity, each Cox model was applied independently to the test dataset.…”
Section: Cox Model Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Stratifying mild cognitive impairment (MCI) subjects according to their conversion risk is of great interest for clinical practice and clinical trials (e.g., patient counseling, initiation of pharmacologic and nonpharmacologic treatments, and inclusion in trials). A recent study by our group evaluated 18 F-FDG PET by voxelwise principle-components analysis (PCA) and validated a PCA-derived AD conversion-related pattern (ADCRP) that showed high accuracy in prediction of conversion from MCI to AD (4). This study was in contrast to other studies (5)(6)(7).…”
mentioning
confidence: 85%
“…18 F-FDG PET scans were spatially normalized to an in-house 18 F-FDG PET template in Montreal Neurological Institute space (8) and smoothed with an isotropic gaussian kernel of 12 mm in full width at half maximum. We assessed the pattern expression score (PES) of the previously validated ADCRP as described before (4).…”
Section: Pet Analysismentioning
confidence: 99%